PENINGKATAN PERAN IBU PKK SEBAGAI UPAYA OPTIMALISASI PEMELIHARAAN KESEHATAN TERHADAP PENYAKIT HIPERTENSI PADA MASA PANDEMIK COVID-19 - Ida Ayu Agung Laksmi; A.A Ngurah Nara Kusuma (Synergy and Society Service, 2022)
Hypertension is known to be one of the most vulnerable comorbidities and is associated with the severity of symptoms experienced by Covid-19 sufferers. The highest health problem in the elderly is hypertension, which is as many as 60 people out of a total of 98 people in Banjar Yeh Dangin, Abianbase Village, Mengwi Badung. The purpose of this community service activity is to empower PKK women as an intervention to optimize health care, especially against hypertension during the Covid-19 pandemic. This activity is carried out in three stages including the assessment stage, implementation stage, and evaluation stage. The assessment stage is carried out to analyze the problems and potentials that exist in Banjar Yeh Dangin, Abianbase Village, Mengwi Badung. The implementation stage is carried out with health education which is divided into 2 days of implementation, namely October 30, 2021 which is accompanied by free health service activities and November 4 which is accompanied by eye screening activities. Evaluation of activities is carried out in a formative manner that focuses on evaluating the process and evaluating the results carried out summatively by comparing the value of knowledge of PKK women before and after being given public education. The conclusion of this activity is that there is an increase in the knowledge of PKK women in Banjar yeh Dangin, Abianbase Village, Mengwi Badung. Therefore, monitoring activities can be carried out to increase the role of PKK in optimizing health care, especially for hypertension in Banjar Yeh Dangin, Abianbase Village, Mengwi Badung.